2017
DOI: 10.1111/tri.13014
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of humoral immune monitoring in kidney transplantation: the role of “hidden” alloreactive memory B cells

Abstract: The advent of novel sensitive assays assessing circulating anti-human leukocyte antigen (HLA) antibodies has allowed recognizing humoral alloimmunity as the main immune-mediated mechanism responsible for allograft rejection and graft loss in kidney transplantation. However, current immune-monitoring techniques, exclusively focusing on circulating anti-HLA antibodies, may underestimate the magnitude of humoral immune response as they exclude the memory B-cell (mBC) pool. Different biological compartments are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…The induction and differentiation of circulating mBCs into antibody-secreting plasmablasts were performed as previously described. [23][24][25] Briefly, peripheral blood mononuclear cells were resuspended at 1.5 Â 10 6 cells/ ml concentration in Iscove's modified Dulbecco's medium (Gibco Invitrogen, Paisley, UK) containing 10% fetal bovine serum (Hyclone, Gibco) supplemented with 2 mmol/l L-glutamine (Gibco Invitrogen), 100 U/ ml penicillin, and 100 mg/ml streptomycin (Gibco Invitrogen). Cells were activated for 6 days with 500 ng/ml a-CD40 mAb (R&D Systems, Minneapolis, MN), 2.5 mg/ml toll-like receptor-9 ligand oligodeoxynucleotides 2006 CpG (Hycult Biotechnology, Uden, the Netherlands), 600 IU/ml IL-2 (Sigma-Aldrich, St. Louis, MO), 25 ng/ml IL-10 (R&D Systems), and 100 ng/ml IL-21 (Gibco Invitrogen).…”
Section: Quantification Of Pla2r-specific Igg By Polyclonally Expandementioning
confidence: 99%
“…The induction and differentiation of circulating mBCs into antibody-secreting plasmablasts were performed as previously described. [23][24][25] Briefly, peripheral blood mononuclear cells were resuspended at 1.5 Â 10 6 cells/ ml concentration in Iscove's modified Dulbecco's medium (Gibco Invitrogen, Paisley, UK) containing 10% fetal bovine serum (Hyclone, Gibco) supplemented with 2 mmol/l L-glutamine (Gibco Invitrogen), 100 U/ ml penicillin, and 100 mg/ml streptomycin (Gibco Invitrogen). Cells were activated for 6 days with 500 ng/ml a-CD40 mAb (R&D Systems, Minneapolis, MN), 2.5 mg/ml toll-like receptor-9 ligand oligodeoxynucleotides 2006 CpG (Hycult Biotechnology, Uden, the Netherlands), 600 IU/ml IL-2 (Sigma-Aldrich, St. Louis, MO), 25 ng/ml IL-10 (R&D Systems), and 100 ng/ml IL-21 (Gibco Invitrogen).…”
Section: Quantification Of Pla2r-specific Igg By Polyclonally Expandementioning
confidence: 99%
“…Antibody levels increased over subsequent weeks, despite the protocolized use of rituximab (anti‐CD20) and an absence of measureable plasma B cells. Again it was concluded that plasma cells or a subset of memory B cells without surface ‐CD20 were producing the antibodies. Recently Koshizuka et al detected donor‐derived anti‐cytomegalovirus (CMV) antibody beyond 6 months post–lung transplantation in 2 recipients and subsequently characterized the presence of donor plasma cells (via their flow cytometry CD19 − /CD138 + profile) in the recipients’ serum.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with our own report, these various case series suggest that donor lymphoid tissue originating memory cells (likely plasma cells) enter and remain in the recipient circulation long term. The case report utilizing rituximab, with no circulating B cells and the 2 case reports observing antibodies within a short 7 days from transplant, argue against the theory that B cells are the bridging cell that subsequently differentiates into plasma cells . Additionally, tissue‐resident B cells are associated with local antigens, so they should not be outside the allograft in significant numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are additional factors that contribute to the development of an alloimmune response beyond genetic polymorphism. This includes both innate and adaptive immune mechanisms (e.g., antigen presentation, immunological memory, complement regulation) as well as nonimmunological factors (e.g., adherence, ischemia-reperfusion injury) [87][88][89][90][91].…”
Section: Future Outlookmentioning
confidence: 99%